Analysis of Customer Loyalty of Indonesia Sharia Bank (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
This study aims to determine the effect of the application of Islamic values on customer loyalty at Indonesian Islamic banks in Medan. This study’s analytical methods are the Instrument and Data Quality Test, Classical Assumption Test, Research Hypothesis Testing, and Multiple Linear Regression Analysis. The results of the analysis on the application of Islamic values at PT Bank Syariah Indonesia in Medan show that the application of Islamic values has a significant effect on customer loyalty at PT Bank Syariah Indonesia in Medan, this can be seen from the application of Islamic values.